2022-RA-638-ESGO Pembrolizumab with multimodal immunomodulation in chemotherapy-pretreated cervical, endometrial, and uterine cancer: the PRIMMO phase II trial. (20th October 2022) - De Jaeghere, Emiel A; Tuyaerts, Sandra; van Nuffel, An MT; Belmans, Ann; Bogaerts, Kris; Baiden-Amissah, Regina; Vuylsteke, Peter; Henry, Stéphanie; Trinh, Xuan Bich; van Dam, Peter A; Aspeslagh, Sandrine; de Caluwé, Alex; et al.
Abstract : Introduction/Background: To decrease immunosuppression and enhance T-cell activation in the tumour microenvironment, we conducted an open-label, investigator-initiated, multicohort, phase II trial (NCT03192059 ) of pembrolizumab with multimodal immunomodulation. Methodology: Chemotherapy-pretreated patients were recruited into two experimental cohorts (cervical carcinoma or endometrial carcinoma) and one exploratory cohort (uterine sarcoma). Patients received an immunomodulatory five-drug cocktail consisting of low-dose cyclophosphamide, aspirin, lansoprazole, vitamin D, and curcumin starting two weeks before radioimmunotherapy ( figure 1 ). Pembrolizumab, 200 mg/dose, was administered on day 1 of each 21-day cycle from day 15 onwards; one of the tumour lesions was irradiated (8Gyx3) on days 15, 17, and 19. The primary endpoint was objective response rate (irORR) per immune-related response criteria (irRC) at week 26; a lower bound of its 90% confidence interval (CI) of >10% in either experimental cohort was considered successful. Results: Fifty patients were enrolled and treated across the cohorts (cervical, n=18; endometrial, n=25; sarcoma=7). Pathology review revealed that 3/7 sarcoma patients had carcinosarcoma. At week 26, the irORR was 11.1% (90%CI, 2.0 to 31.0) in cervical cancer, 12.0% (90%CI, 3.4 to 28.2) in endometrial cancer, and 14.3% (90% CI, 0.7 to 52.1) in uterine (carcino)sarcoma. The best overall response rate per RECIST v1.1 was 22.2% (90%CI, 8.0 to 43.9), 12.0% (90%CI, 3.4 to 28.2), and 28.6 (90%CI, 5.3 to 65.9). Median PFS was 13.4 weeks (11.3 to 26.1), 13.1 weeks (13.1 to 19.4), and 34.3 weeks (95%CI, 5.6 to 77.9) ( figure 2A-C ). Grade≥3 treatment-related adverse events were reported in 10 (55.6%), 9 (36.0%), and 4 (57.1%) patients. Overall, there was one (2.0%) possible treatment-related death. Health-related quality of life was generally stable over time. Multi-parameter immune monitoring characterised the patients and revealed changes throughout study treatment. Conclusion: PRIMMO did not show sufficient evidence of a positive risk-to-benefit ratio to recommend a confirmatory phase III trial.